Interconnection viability of high demand isolated area through a HVDC-VSC link - Juan A. Varela; Mario A. Rios (Institute of Advanced Engineering and Science, 2021)
Electrically isolated areas are separated by a great distance and, normally, have a considerably low demand; in consequence, these are non-interconnected from the main power grid or electrical national transmission systems. Great distance and low demand are the reasons why an interconnection project in high voltage AC is not feasible in most of these cases. Nevertheless, there are some isolated areas with high power demand and even though they are separated from the main grid by large distances and hard terrains; however, it is still reasonable to think about an interconnection project. This paper had developed a methodology that allows the evaluation of viability, technically and economically, of a HDVC-VSC interconnection project for great distance and high demand considering overhead and/or underground DC line. The methodology was applied to a case of study in Peru, based on the projected interconnection between Moyobamba and the isolated area of Iquitos; showing that HVDC is a feasible alternative.